Epistemologies of Struggle: Social Movement Theory and the Politics of Knowledge Production. Issue 2 (May 2023) - Brissette, Emily; King, Mike
Within the field of US social movement studies, there is periodic concern that the work produced by scholars is not more widely read and used by activists and organizers, yet there is little attention given to how epistemological norms within the field produce and maintain the disconnect between mainstream US social movement studies and movements on the ground. In this paper we trace the major contours of the problem: the positivism that saturates the field's tendency towards abstraction and model building; the implicit normative commitment to a liberal-pluralist social order which eclipses radical voices; and the refusal to engage seriously with the organic knowledge production that takes place within every movement. We also highlight exemplary theorizing that has emerged out of active struggles and argue that the humanistic study of social movements must begin from a place of intellectual humility, decentering academic expertise and recognizing that scholars have much to learn from organic intellectuals in movements today.